Methodologies for Studying Visual Expertise - Andreas Gegenfurtner; Jeroen J. G. van Merriënboer (EARLI, 2017)
Visual expertise can be defined as maximal adaptation to the requirements of a vision-intensive task. The process of developing a "good eye" in vision-intensive tasks is proposed, indicated, and elaborated by various measures contingent on diverse methodological arenas, all of which attempt to advance our understanding of what constitutes visual expertise. The aim of this special issue is to provide a reflection on this methodological pluralism and to offer a discussion of the affordances and constraints of some of these methodological approaches. Specifically, grounded on the medical domain, this special issue brings together a selection of nine articles that discuss cognitive-neurosciences, receiver operating characteristics (ROC) analysis, eye tracking, pupillometry, the flash-preview moving window paradigm, the combination of eye tracking data and verbal report data, the use of interviews and verbal protocols, ethnomethodology, and the expert performance approach. Two commentaries conclude the special issue. As an introduction, this article presents a comparative metaphorical mapping of visual expertise research. Metaphors are a useful tool for mirroring in simple terms the often complex paradigms underlying theory and applied research practice. We first identify four metaphors used in the analysis of visual cognition: activation, detection, inference, and practice. These metaphors are described with an empirical example and discussed to elicit (partly tacit) assumptions associated with prototypical method decisions. We then link the proposed metaphorical mapping to the contributions in this special issue.